Sterilizing elastomeric chains without losing mechanical properties. Is it possible? - Pithon,Matheus Melo (2015)
OBJECTIVE: To investigate the effects of different sterilization/disinfection methods on the mechanical properties of orthodontic elastomeric chains. METHODS: Segments of elastomeric chains with 5 links each were sent for sterilization by cobalt 60 (Co60) (20 KGy) gamma ray technology. After the procedure, the elastomeric chains were contaminated with clinical samples of Streptococcus mutans. Subsequently, the elastomeric chains were submitted to sterilization/disinfection tests carried out by means of different methods, forming six study groups, as follows: Group 1 (control - without contamination), Group 2 (70°GL alcohol), Group 3 (autoclave), Group 4 (ultraviolet), Group 5 (peracetic acid) and Group 6 (glutaraldehyde). After sterilization/disinfection, the effectiveness of these methods, by Colony forming units per mL (CFU/mL), and the mechanical properties of the material were assessed. Student's t-test was used to assess the number of CFUs while ANOVA and Tukey's test were used to assess elastic strength. RESULTS: Ultraviolet treatment was not completely effective for sterilization. No loss of mechanical properties occurred with the use of the different sterilization methods (p > 0.05). CONCLUSION: Biological control of elastomeric chains does not affect their mechanical properties.